Aesthetics of Space Organization: Lessons from Traditional European Cities - Hourakhsh Ahmad Nia; Yousif Hussien Suleiman (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
For centuries the aesthetic significance of space organization has been one of the significant subjects of study for most artists, architects, urban designers and philosophers. Cities which experience diverse stages of growth transmit dissimilar aesthetic values due to their locations, culture, history and background. This research will try to take out the aesthetic values of the traditional European cities through the literature on aesthetic of the urban design. Accordingly, this study reflects the term urban aesthetics in spatial organization. It tries to answer the question of how space organization can lead to the aesthetic understanding of a place. The methodology for this study developed based on grounded theory study and qualitative assessments of European cities through the literature review. Overall, the study assessed integration, visual connectivity, vitality, spatial quality, as the main factors in shaping the aesthetic quality of the urban environment in European traditional cities. At the end, it proposed the findings to apply in contemporary urban designing.